Direct Target Network of the Neurospora crassa Plant Cell Wall Deconstruction Regulators CLR-1, CLR-2, and XLR-1 - James P. Craig; Samuel T. Coradetti; Trevor L. Starr; N. Louise Glass (mBio, 2015)
ABSTRACT Fungal deconstruction of the plant cell requires a complex orchestration of a wide array of intracellular and extracellular enzymes. In Neurospora crassa, CLR-1, CLR-2, and XLR-1 have been identified as key transcription factors regulating plant cell wall degradation in response to soluble sugars. The XLR-1 regulon was defined using a constitutively active mutant allele, resulting in hemicellulase gene expression and secretion under noninducing conditions. To define genes directly regulated by CLR-1, CLR-2, and XLR-1, we performed chromatin immunoprecipitation and next-generation sequencing (ChIPseq) on epitope-tagged constructs of these three transcription factors. When N. crassa is exposed to plant cell wall material, CLR-1, CLR-2, and XLR-1 individually bind to the promoters of the most strongly induced genes in their respective regulons. These include promoters of genes encoding cellulases for CLR-1 and CLR-2 (CLR-1/CLR-2) and promoters of genes encoding hemicellulases for XLR-1. CLR-1 bound to its regulon under noninducing conditions; however, this binding alone did not translate into gene expression and enzyme secretion. Motif analysis of the bound genes revealed conserved DNA binding motifs, with the CLR-2 motif matching that of its closest paralog in Saccharomyces cerevisiae, Gal4p. Coimmunoprecipitation studies showed that CLR-1 and CLR-2 act in a homocomplex but not as a CLR-1/CLR-2 heterocomplex. IMPORTANCE Understanding fungal regulation of complex plant cell wall deconstruction pathways in response to multiple environmental signals via interconnected transcriptional circuits provides insight into fungus/plant interactions and eukaryotic nutrient sensing. Coordinated optimization of these regulatory networks is likely required for optimal microbial enzyme production.